Digitalisasi Informasi Kampung Adat Kasepuhan Sinar Resmi Unesco Global Geopark Ciletuh-Palabuhanratu - Adhitia Erfina; Retna Ayu Puspatarini; Tarikh Agustia Ijudin; Pratama Haditua Reyner Siregar (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Geopark is an area that has geological elements in which local people are invited to participate to protect and improve the function of the natural and cultural heritage in it. Kasepuhan Sinar Resmi is part of the cultural aspect that is inseparable from the Ciletuh Geopark which is still being preserved. The village always gets lots of visitors who want to know the original Sundanese culture, because the Kasepuhan Sinar Resmi Community still carries out the traditions of their ancestors. Nevertheless, the Kasepuhan Sinar Resmi Community does not close itself off from developments from the outside such as the use of technology in the village. The crafts of the local community have also started to be sold online and have good packaging. However, several problems have arisen, with the large number of tourists visiting the Kasepuhan Sinar Resmi making it often difficult for local traditional leaders to deal with them. In addition, selling products online is often used as a crime by some people who fake authentic products made by Kasepuhan Sinar Resmi. Another problem is that there is no real-time information management that is distributed globally to inform the activities being held and what facilities are available at Kasepuhan Sinar Resmi. This problem can be anticipated with a Web-Based Information System to be able to accommodate the needs of tourists as a Digital Information Source which can also be managed by the Kasepuhan Sinar Resmi community for Reservation services and online Product Marketing Media.